Country Economic Memorandum for Sao Tome and Principe - Background Note 14 : The Case for Economic Inclusion of Sexual and Gender Minorities in São Tomé and Príncipe - Cortez, Clifton John; Arzinos, John (Ioannis) (World Bank, Washington, DC, 2019)
The purpose of this analysis is to provide a snapshot of exclusion based on SOGI in São Tomé and Príncipe (STP) and the opportunities for SOGI inclusion especially in the tourism sector. The main questions for the reader to consider are: Why is the World Bank involved in SOGI? How can STP benefit from SOGI inclusion? What can be done to ensure SOGI inclusion in STP? Finally, the central takeaway from this analysis is that excluding sexual and gender minorities negatively impacts economic development and poverty reduction, whereas including them is beneficial to economic development and poverty reduction. The theoretical argument is that exclusion costs money. Exclusion based on sexual orientation and gender identity often begins as early as the primary school years and continues in the workplace, as well as more broadly in the economy and in society. As a result, sexual and gender minorities face significant stigma that prevents them from realizing their productive potential and limits their ability to contribute to the economy and to society. When anyone is excluded from the labor force based on indelible personal characteristics unrelated to ability, such as sexual orientation or gender identity, both the economy and social cohesion suffer.